The treatment of socio-scientific issues in science teacher training: opportunities and challenges in the voices of undergraduates - Michel; Washinton Luiz (Uni-pluriversidad, 2014)
The perspective STSE (Science-Technology-Society-Environment) was recently implemented in the training courses for science teachers in Brazil, and proposes greater coordination of scientific knowledge with subjective questions that constitute the science, enables discussion of the nature of science and its implications for social and environmental issues. The present work aims to contribute to training of science teachers that approximates the current demands of contemporary society. Having as theoretical reasons the implications of STSE Movement in science teaching, we bring some considerations on pedagogical practices of undergraduates in Biological Sciences held within its Supervised. Through content analysis of the speeches of undergraduates, we can identify contributions and limitations that treatment of socio-scientific issues (SSI) revealed in the process, putting to discuss some aspects that are tangent training teachers committed to a contextualized view of science and scientific training. It discusses, among them, the relationship theory and practice insupervised training of future teachers’ conceptions about the implications of the STSE perspective in science teaching and science teacher positioning ahead controversial themes.